Barley Allelochemicals of Gramine and Hordenine: Their Effects on Broiler Chickens - Chaniago, I; Lovett, JV; Roberts, JR (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
An experiment aimed at examining the effects of gramine and hordenine, incorporated into diets, on the growth and histological structures of the chicken liver has been carried out at the animal house complex, Analytical Laboratory, and Histology laboratory of the University of New England, Armidale, Australia. Five treatment groups (50 and 500 ppm hordenine or gramine, and standard feed as control) were administered to one-week old broiler chickens. Each treatment group had six heads of chickens and were replicated 6 times. Data collected including body weight and feed intake (recorded weekly), liver tissue collection for histological examination, and determination of gramine and hordenine in the liver. Data were analysed using Analysis of Variance (ANOVA) at 5% level of confident. Results demonstrated that gramine had more effects than hordenine on the animal tested. A high concentration (500 ppm) of either gramine or hoedenine was sufficient to induce changes in liver structure of the chickens as indicated by cell vacuolation even though they were not necessarily associated with reduced feed intake or growth rate of the animals. Scab-like lesions on their feet during weeks 4 and 5 of the experiment were observed from the group of 500-ppm gramine.Key Words : gramine, hordenine, chicken